Mixing and controlling the pH of citrate and phosphate with website - Syahrul Syahrul; Ilham Komarujaman (Journal of Robotics and Control (JRC), 2021)
In this study built an instrument capable of mixing and controlling chemical pH of citrate solution and phosphate solution as buffer solution. The problem often experienced in mixing chemicals is a matter of safety and the accuracy of the concentration of the mixing of the substance. The function of this instrument is to mix and control the pH of the citrate and phosphate solution. It is hoped that in the presence of this instrument, the manufacture of citrate solutions and phosphate solutions can be carried out electronically which does not involve manual calculations to obtain the desired pH of the solution, and is relatively safe from direct contact with chemicals. This instrument is built using a pH sensor as the sensing pH value of the solution to be made. And as a controller used microcontroller. Results of pH control other than can be stored in the database, can also be transmitted to the internet (website) using a wifi interface device. Mixers and pH controls of citrate and phosphate have been realized and resulted in good pH control.